ANALISIS PENGARUH PEMBAYARAN NON-TUNAI (ATM, KREDIT DAN E-MONEY) TERHADAP JUMLAH UANG BEREDAR DI INDONESIA - Vira Shalsyabila Rama Putri (2021)
The level of technological progress is one of the important factors that can affect the pace of the economy because technological advances in a country can encourage innovation in existing developments in the financial sector by developing payment systems consisting of ATMs, Credit and E-Money. This study aims to determine the effect of ATM/debit cards, credit cards and e-money on the amount of money in circulation (M1) in Indonesia. This study uses data from 2010 to 2019 in quarterly form. The method used in this study is a multiple linear regression analysis model using the OLS method. The results of multiple regression analysis show that (1) there is a significant effect between ATM/debit cards on the amount of money in circulation (M1) (2) there is a significant effect between credit cards on the amount of money in circulation (3) there is a significant effect between e-money on Amount of Money Supply.